Design and Development of a Computerised Instrumentation System for Spray Charge Measurement - Maski, Devanand; Durairaj, C Divakar (Journal of Agricultural Engineering, 2004)
Electrically charged sprays can provide greater control of droplet transport and can reduce spray wastage. In developing countries, the main lacuna in the development of electrostatic charging systems is the non-availability of relevant research facilities, particularly concerning instrumentation. A simple, easy to build instrumentation setup was developed using off-the shelf components and products available in Indian market. It consisted of a Faraday's cage to collect the spray charge, a charge-voltage converter circuit to convert the charge to a corresponding voltage and a computerized data logging system to record the spray charge level at continuous time intervals. The developed system was evaluated on an electrostatic charging attachment to a knapsack mist-blower. The system clearly showed that the chargemass ratio induced on the spray fluid increased linearly with charging voltage upto a critical value of 3.5 to 4.0 kV. It increased as the flow rate was decreased from 300 ml min¯¹ to 60 ml min¯¹. The time-wise record of charging phenomenon helped to understand aspects such as electrode wetting, shorting and electrode loading patterns.